Acceptance Analysis of Learning Management System in Project-based Learning - Nugroho, Rengga Prakoso; Nurhidayah, Siti; Soepriyanto, Yerry; Purnomo, Purnomo (JURNAL FASILKOM, 2024)
This research specifically aims to find out which factors significantly influence the acceptance of LMS developed by the learning team of the Graphic and Visual Media Innovation course at the State University of Malang. The course learning uses two management systems, namely LMS and Progress Report Card (PRC). Acceptance analysis is conducted because the LMS used is a product prototype that has just been implemented in the first semester student lectures. The research was conducted using the technology acceptance model framework. The analysis process uses a quantitative approach with hypothesis testing through multiple linear regression tests. There are two variables observed, namely usefulness (X1), ease of use (X2) and tendency to use (Y). From the analysis process that has been carried out, the results show that the two independent variables (X1 & X2) simultaneously have a significant influence on the dependent variable (Y). However, there is a finding that ease of use (X2) does not significantly affect the usage tendency variable (Y). For further studies, it should be conducted with a more massive scope, not only focusing on one narrow context, using more variables and external factors, and focusing on the learner experience.